Self-perception of the control of conventionality by the Inter American Court: Brief critical apostilles - Eto Cruz, Gerardo (2019)
This article presents the official transcription of the judgments that the Inter American Court of Human Rights (IACHR) has disclosed through the IACHR Case Law Booklet No. 7: Control of Conventionality, the presentation of which was edited by professor Claudio Nash and signed by Humberto A. Sierra Porto, the President of the referred Court at the time. For our part, we have written a prior and brief comment to said judgments or conventional sentences, which we are fully responsible for as authors. The purpose is to incorporate a minimum contrast to our constitutional case law, under the modern paradigm of guided conventional control, particularly, for magistrates and prosecutors with a view to gradually boosting the diffuse conventionality control doctrine.